Investigation in to ramp queues vs. freeway queues on ramp metered freeways - Lim, David Eng Chung (Curtin University, 2010)
Freeways and highways form an integral part of any road network system demanding significant quantities of resources to plan and construct. During times of congestion and flow breakdown forms of traffic management are required to maintain the efficiency, reliability and safety of these high asset road facilities. Here within lies the responsibilities of traffic engineering professionals. The lack of adequate maintenance and management of any urban road network system hinders economic development and quality of life.Ramp metering is an active traffic management system implemented on high speed, free flowing facilities such as freeways and highways. This form of intelligent transport system has been applied to freeways throughout the world to regulate the intensity and demand proportion of freeway inflow during peak demand periods. The primary goal is to manage the existing roadway to operate at maximum efficiency. Main Roads Western Australia, the governing road authority in Western Australia is currently in a position to investigate the suitability of ramp metering on Western Australia's freeways.This research demonstrates how traffic movement and interaction can be mapped and characterised to identify forms of traffic flow breakdown that ramp metering has the potential to address. This research also documents the required components of ramp metering, how it should operate and the potential this active management system has to be applied over a system wide road network infrastructure.The Mitchell Freeway southbound direction undergoes significant forms of congestion and traffic flow breakdown during the morning peak period. A traffic characteristic of the Mitchell Freeway was developed to make an evaluation for the suitability of ramp metering as an effective management system. An analytical comparison between current freeway queues and theoretical on-ramp queues provided indication that the congestion and flow breakdown currently observed had the potential to be managed through ramp metering, ensuring the future sustainability of this vital freeway for the city of Perth, Western Australia.